Drive : the surprising truth about what motivates us - Pink, Daniel H. (New York, NY : Riverhead Books, 2009)
Pink argues that the secret to high performance and satisfaction in today's world is the deeply human need to direct our own lives, to learn and create new things, and to do better by ourselves and our world.
As Daniel H. Pink explains in his new and paradigm- shattering book Drive: The Surprising Truth About What Motivates Us, the secret to high performance and satisfaction in today's world is the deeply human need to direct our own lives, to learn and create new things, and to do better by ourselves and our world. Drawing on four decades of scientific research on human motivation, Pink exposes the mismatch between what science knows and what business does--and how that affects every aspect of our lives. He demonstrates that while the old-fashioned carrot-and-stick approach worked successfully in the 20th century, it's precisely the wrong way to motivate people for today's challenges. In Drive, he reveals the three elements of true motivation: a) Autonomy: the desire to direct our own lives; b) Mastery: the urge to get better and better at something that matters; and c) Purpose: the yearning to do what we do in the service of something larger than ourselves. Along the way, he takes us to companies that are enlisting new approaches to motivation and introduces us to the scientists and entrepreneurs who are pointing a bold way forward.
Introduction : the puzzling puzzles of harry Harlow and Edward Deci -- pt. 1. A new operating system -- 1. The rise and fall of motivation 2.0 -- 2. Seven reasons carrots and sticks (often) don't work-- 2A. --and the special circumstances when they do -- 3. Type I and Type X -- pt. 2. The three elements -- 4. Autonomy -- 5. Mastery -- 6. Purpose -- pt. 3. The Type I toolkit -- Type I individuals : nine strategies for awakening your motivation -- Type I for organizations : nine ways to improve your company, office, or group -- The Zen of compensation : paying people the Type I way -- Type I for parents and educators : nine ideas for helping our kids -- The Type I reading list : fifteen essential books -- Listen to the gurus : six business thinkers who get it -- The Type I fitness plan : four tips for getting (and staying) motivated to exercise -- Drive : the recap -- Drive : the glossary-- The Drive discussion guide : twenty conversation starters to keep you thinking and talking -- Find out more--about yourself and this topic -- Acknowledgments -- Notes -- Index.
Includes bibliographical references (p. [221]-229) and index.
Keywords: Motivation (Psychology); Motivation